Policy on the Formulation of Criminal Law Enforcement and Human Rights in the Utilization of the Environment and Natural Resources by Multinational Companies (Law Research Review Quarterly, 2015)
Modernization and development have brought many disasters to the environment and humanity, in this case, the environment is interpreted conventionally. The environment is considered as an object. This perspective views and places the environment as an object that connotes commodities and can be exploited to merely support development. The environment as a system is certainly subject to a natural legal system it is destined. The system can run in a balanced manner, if the quality of the components inside it continues to run stable. As a living system, the environment is a life that consists of past life, present life, and future life.